Pengaruh Model Kooperatif Tipe Jigsaw Berbantuan Media Engklek Matematika Terhadap Kemampuan Komunikasi Matematis Siswa Kelas IV - Fadliansyah, Fauzi; Noviyanti, Elsa (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
This research shows that the application of the Jigsaw type cooperative learning model assisted by mathematical engklek media significantly improves students' mathematical communication abilities. After conducting an interview with the fourth grade teacher at SDN Cibeber III Cilegon with the initials "NH" it can be seen that the students' mathematical communication abilities are not yet optimal. he said that "students' mathematical communication abilities vary, some can do it, some can't. When working on questions, students need help with the steps to solve them." This statement is reinforced by the results of students' initial ability tests. After the researchers observed the results of the test, it was found that 26 of the 36 students who took the initial mathematical communication ability test were not able to use mathematical notation or symbols and operations correctly, then the students also did not show what they knew and what was asked of them. question. This research was successful with the average result of the experimental class reaching 76.53 compared to an average of 60.00 in the control class. These findings emphasize the importance of interactive and fun learning strategies to overcome the low mathematical communication skills that students have experienced. The method used in this research is an experiment with a quasi experimental design. The population used is class IV students at SDN Cibeber III Cilegon for the 2023/2024 academic year. The sampling technique uses a purposive sampling technique by determining the number of samples using the Slovin formula. Data collection techniques in this research used tests and documentation